Repurposing Artemisinin and its Derivatives as Anticancer Drugs: A Chance or Challenge? - Ma, Zhaowu; Woon, Clariis Yi-Ning; Liu, Chen-Guang; Cheng, Jun-Ting; You, Mingliang; Sethi, Gautam; Wong, Andrea Li-Ann; Ho, Paul Chi-Lui; Zhang, Daping; Ong, Peishi; Wang, Lingzhi; Goh, Boon-Cher (Frontiers in Pharmacology, 2021)
Cancer has grown to become a global health issue, accounting for one out of six deaths. Despite the recent advances in oncology, there is still an ever-growing need for new therapies that can be made readily accessible. The process of drug discovery and development is arduous and takes many years, and while it is ongoing, the timeframe for lead compounds to reach the point of clinical trials is very long. Drug repurposing has gained traction as it expedites and hastens the process of discovering new entities potentially used for anticancer therapy. One such potential candidate is the antimalarial, artemisinin that has shown to exert anticancer effects in vitro and in vivo. In this review, major molecular and cellular mechanisms of anticancer effect induced by artemisinin and its derivatives have been summarized. Furthermore, major mechanisms of action and some key signalling pathways that this group of compounds work by have been reviewed to explore potential targets which contribute to the proliferation and metastasis of tumour cells. Pharmacokinetic properties, anticancer potency and current formulations that hinder the clinical translation of artemisinin as an anticancer agent, despite its established profile in malaria treatment, are also discussed. Finally, potential solutions or new strategies have been identified to overcome the bottlenecks in repurposing artemisinin‐type compounds as anticancer drugs.